The Tension Forces Acting on the Belt Conveyor Rollers - Nematovich, Ataqulov Lazizjon; Bahridinovich, Haydarov Shohidjon; Arzimurodovich, Omonov Do‘stmurod (International Journal on Integrated Education, 2023)
This article determines the distribution of the forces applied to the cross-sectional surface of the belt, when rocks are transported by belt conveyors, the effect of dynamic forces on the bending of the belt and middle roller length rocks on the basis forces the roller supports.